Simultaneous acquisition of perfusion image and dynamic MR angiography using time‐encoded pseudo‐continuous ASL - Suzuki, Y; Helle, M; Koken, P; Van Cauteren, M; Van Osch, M (Wiley, 2017)
Purpose Both dynamic magnetic resonance angiography (4D‐MRA) and perfusion imaging can be acquired by using arterial spin labeling (ASL). While 4D‐MRA highlights large vessel pathology, such as stenosis or collateral blood flow patterns, perfusion imaging provides information on the microvascular status. Therefore, a complete picture of the cerebral hemodynamic condition could be obtained by combining the two techniques. Here, we propose a novel technique for simultaneous acquisition of 4D‐MRA and perfusion imaging using time‐encoded pseudo‐continuous arterial spin labeling. Methods The time‐encoded pseudo‐continuous arterial spin labeling module consisted of a first subbolus that was optimized for perfusion imaging by using a labeling duration of 1800 ms, whereas the other six subboli of 130 ms were used for encoding the passage of the labeled spins through the arterial system for 4D‐MRA acquisition. After the entire labeling module, a multishot 3D turbo‐field echo‐planar‐imaging readout was executed for the 4D‐MRA acquisition, immediately followed by a single‐shot, multislice echo‐planar‐imaging readout for perfusion imaging. The optimal excitation flip angle for the 3D turbo‐field echo‐planar‐imaging readout was investigated by evaluating the image quality of the 4D‐MRA and perfusion images as well as the accuracy of the estimated cerebral blood flow values. Results When using 36 excitation radiofrequency pulses with flip angles of 5 or 7.5°, the saturation effects of the 3D turbo‐field echo‐planar‐imaging readout on the perfusion images were relatively moderate and after correction, there were no statistically significant differences between the obtained cerebral blood flow values and those from traditional time‐encoded pseudo‐continuous arterial spin labeling. Conclusions This study demonstrated that simultaneous acquisition of 4D‐MRA and perfusion images can be achieved by using time‐encoded pseudo‐continuous arterial spin labeling. Magn Reson Med 79:2676–2684, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.